1963
DOI: 10.1002/aic.690090324
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in experimental reactors

Abstract: showing that reactor-product distribution is generally distorted in proportion to a reactor Peclet number. G. I. Taylor's theory of axial mixing is used to relate this Peclet number to the physical characteristics of the reactor.Although the effects of axial mixing are concluded to be negligible in most commercial or large-scale equipment, they are serious in the case of experimental or pilot-scale apparatus.Charts are drawn to illustrate design problems for these reactors. PURPOSE AND SCOPEThe successful scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1971
1971
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…According to Tichacek's approximation (Tichacek, 1963), the fractional reduction in the maximum yield of intermediates due to axial mixing was small (below 0.05) in cases where the N values were larger than 11. Therefore, it was concluded that axial mixing did not affect the yield of target intermediates under the examined conditions.…”
Section: Residence Time Distributionmentioning
confidence: 99%
“…According to Tichacek's approximation (Tichacek, 1963), the fractional reduction in the maximum yield of intermediates due to axial mixing was small (below 0.05) in cases where the N values were larger than 11. Therefore, it was concluded that axial mixing did not affect the yield of target intermediates under the examined conditions.…”
Section: Residence Time Distributionmentioning
confidence: 99%
“…A formula of Tichacek (1963) relating selectivity loss to dispersion caused by eddies or bypassing was used. A formula of Tichacek (1963) relating selectivity loss to dispersion caused by eddies or bypassing was used.…”
Section: Methodsmentioning
confidence: 99%
“…Logical extensions of such work would be to determine temperature and concentration distributions in the stirred tank and correlate the data in a similar manner. Other workers ( 3 to 13) have analyzed the stirred-tank system from a macroscopic viewpoint. Power re uirements this approach, and energy and mass transfer processes have been studied.…”
Section: Hydrodynamic Measurementsmentioning
confidence: 99%